2014
DOI: 10.1086/674320
|View full text |Cite
|
Sign up to set email alerts
|

Infection withMycoplasma gallisepticumBuffers the Effects of Acute Stress on Innate Immunity in House Finches

Abstract: When wild animals become infected, they still must cope with the rigors of daily life, and, thus, they still can be exposed to acute stressors. The suite of physiological responses to acute stress includes modifying the innate immune system, but infections can also cause similar changes. We examined the effects of an acute stressor (capture stress) on leukocyte abundance and bacteria-killing ability (BKA) in wild birds (house finches Haemorhous mexicanus) with and without a naturally occurring infection (Mycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…30 min, 60 min or even 2.5 h after capture). Several of these studies reported a discernible difference in immune function between individuals sampled within 3 min of capture versus those sampled 30 min or more after capture, especially in the case of bactericidal activity (Buehler et al, 2008;Davis, 2005;Fratto et al, 2014;Matson et al, 2006;Millet et al, 2007). It remains unknown whether measures of innate immune function in wild birds vary with capture stress over shorter time intervals; however, it is variation over these shorter time intervals that is likely to be the most relevant for field studies using mist nets or walk-in traps, given that welfare considerations dictate individuals be processed expeditiously post-capture, with the result that blood samples are more likely to be collected within minutes rather than hours of capture.…”
Section: Introductionmentioning
confidence: 99%
“…30 min, 60 min or even 2.5 h after capture). Several of these studies reported a discernible difference in immune function between individuals sampled within 3 min of capture versus those sampled 30 min or more after capture, especially in the case of bactericidal activity (Buehler et al, 2008;Davis, 2005;Fratto et al, 2014;Matson et al, 2006;Millet et al, 2007). It remains unknown whether measures of innate immune function in wild birds vary with capture stress over shorter time intervals; however, it is variation over these shorter time intervals that is likely to be the most relevant for field studies using mist nets or walk-in traps, given that welfare considerations dictate individuals be processed expeditiously post-capture, with the result that blood samples are more likely to be collected within minutes rather than hours of capture.…”
Section: Introductionmentioning
confidence: 99%
“…The house finch–MG interaction has become an important natural model of coevolution between a host and an emerging pathogen, facilitating insights into fundamental issues in disease ecology and evolutionary biology ( 18 , 20 , 21 ). However, we still have only a limited understanding of the key immunological features of the house finch response to MG. Several studies show that house finch immune responses to MG are associated with hematological changes ( 22 , 23 ) and antigen-specific antibody production in both lachrymal fluid and blood ( 9 , 24 ). Nevertheless, the protective effects of humoral immunity remain unclear ( 19 ).…”
Section: Introductionmentioning
confidence: 99%